Modulatory role of adiponectin on endocrine resistance in breast cancer - Forestiero, Martina; Catalano, Stefania; Mauro, Loredana (Università della Calabria, 2024)
EstrogenReceptor (ER) represents a breast cancer positive prognostic factor and the main molecular target of endocrine therapy, although de novo and acquired resistance to this treatment remains a major challenge. Breast Cancer Stem Cells (BCSCs) are blamed to be the driving force behind breast tumor initiation, progression, metastasis, endocrine resistance, and recurrence, due to their strong selfrenewal and multilineage differentiation properties. Notably, it has been evidenced that tumor microenvironment (TME) influences BCSCs behavior, regulating the complex interaction between stromal and breast epithelial cells, through the secretion of different cytokines and growth factors. The most abundant cellular component of TME is represented by adipocytes which became dysfunctional in obesity, leading to an unbalanced adipokines secretion. Particularly, plasma levels of adiponectin, the main adipocytederived factor, are reduced in obese compared to normal weight subjects, promoting growth and progression in ERαpositive breast cancer. This let us to wonder if the induced proliferative effect of low level of adiponectin on ERαpositive breast cancer cells could be related to specific stimulatory effects on breast cancer stemness. In tamoxifenresistant MCF7 (TR MCF7) mammospheres adiponectin increased Mammospheres Forming Efficiency (MFE) and selfrenewal capacity concomitant with an enrichment in CD44+/CD24/ ALDH1+ subpopulation, identifying a typical stemlike phenotype. This was not observed in hormoneresponsive MCF7 (WT MCF7) cells. An increase in mRNA levels of stemness and EpithelialMesenchymal Transition (EMT) markers corroborated the increased percentage of BCSCs in TR compared to WT MCF7 mammospheres. Consistent with these data hormoneresistant cells showed a G0/G1 arrest and an apoptosis reduction compared to WT cells, as evidenced by cell cycle and Annexin V assay, Western Blotting and proteomic analysis. Interestingly, in adiponectintreated TR MCF7 mammospheres, it has been observed a reduced ROS production, concomitant with a slight enhance of mitochondrial membrane potential, confirming the antiapoptotic features of BCSCs. Finally, TR MCF7 cells, obtained from secondary generation mammospheres, exhibited a reduced proliferation rate, Ki67 level and cell motility, suggesting a cellular state of quiescence in TR MCF7 cells. Overall, we demonstrated that low levels of adiponectin promote stemlike features in TR MCF7 cells, that may contribute to relapse. Thus, the study of the molecular mechanisms involved in the regulation of cell death and in the entry of a quiescent state, could pave the way for the development of successful therapies for the treatment of hormoneresistant obese breast cancer patients.
Università della Calabria. Department of Pharmacy, Health and Nutritional Sciences Ph.D. in Translational Medicine XXXVI Cycle
Keywords: breast cancer; estrogen receptor; endocrine resistance; stemness